2016
DOI: 10.1016/j.brainres.2015.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuits in auditory and audiovisual memory

Abstract: Working memory is the ability to employ recently seen or heard stimuli and apply them to changing cognitive context. Although much is known about language processing and visual working memory, the neurobiological basis of auditory working memory is less clear. Historically, part of the problem has been the difficulty in obtaining a robust animal model to study auditory short-term memory. In recent years there has been neurophysiological and lesion studies indicating a cortical network involving both temporal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 119 publications
(172 reference statements)
1
10
0
Order By: Relevance
“…This result may be compatible with previous findings indicating multior supramodal properties of the dorsofrontal networks that have been usually associated with selective spatial attention in the visual modality (e.g., Bharadwaj et al, 2014;Lee et al, 2012;Lewald et al, 2018;Macaluso, 2010;Slotnick & Moo, 2006). For the monkey DLPFC, it has been suggested that neuronal processes exist for visual and auditory location information and spatial working memory (Fuster et al, 2000;Kikuchi-Yorioka & Sawaguchi, 2000;Artchakov et al, 2007;Hwang & Romanski, 2015; for review, see Plakke & Romanski, 2016), and the human DLPFC has been shown to be involved in transforming auditory and visual inputs into multimodal spatial representations that can be used to guide saccades (Tark & Curtis, 2013). The monkey DLPFC receives projections from posterior auditory cortex areas known to be involved in spatial processing and from the posterior parietal cortex (Chavis, & Pandya, 1976;Rauschecker, et al, 1995;Romanski, Bates, et al, 1999;Romanski, Tian, et al, 1999).…”
Section: Cortical Sources Of Training-induced N2 Enhancementsupporting
confidence: 91%
“…This result may be compatible with previous findings indicating multior supramodal properties of the dorsofrontal networks that have been usually associated with selective spatial attention in the visual modality (e.g., Bharadwaj et al, 2014;Lee et al, 2012;Lewald et al, 2018;Macaluso, 2010;Slotnick & Moo, 2006). For the monkey DLPFC, it has been suggested that neuronal processes exist for visual and auditory location information and spatial working memory (Fuster et al, 2000;Kikuchi-Yorioka & Sawaguchi, 2000;Artchakov et al, 2007;Hwang & Romanski, 2015; for review, see Plakke & Romanski, 2016), and the human DLPFC has been shown to be involved in transforming auditory and visual inputs into multimodal spatial representations that can be used to guide saccades (Tark & Curtis, 2013). The monkey DLPFC receives projections from posterior auditory cortex areas known to be involved in spatial processing and from the posterior parietal cortex (Chavis, & Pandya, 1976;Rauschecker, et al, 1995;Romanski, Bates, et al, 1999;Romanski, Tian, et al, 1999).…”
Section: Cortical Sources Of Training-induced N2 Enhancementsupporting
confidence: 91%
“…In a similar vein, frontal activation during mismatch processing has previously been described as reflecting an orienting response (Rinne, Alho, Ilmoniemi, Virtanen, & Näätänen, 2000). At the cellular level, animal studies have documented neural responses to auditory stimulation in the ventrolateral prefrontal cortex, which may play an important role in auditory working memory (for review see Plakke & Romanski, 2016). Indeed, multiple studies have confirmed the involvement of the right IFG in auditory change detection in humans (Doeller et al, 2003;Opitz et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…The activation pattern largely resembles our findings. At the cellular level, animal studies have documented neural responses to auditory stimulation in the ventrolateral prefrontal cortex, which may play an important role in auditory working memory (for review see Plakke & Romanski, 2016). In a similar vein, frontal activation during mismatch processing has previously been described as reflecting an orienting response (Rinne, Alho, Ilmoniemi, Virtanen, & Näätänen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Regions of interest for the ROI analysis were dorsolateral PFC (dlPFC), ventrolateral PFC (vlPFC), orbitofrontal cortex (OFC), and vmPFC in cortex, and putamen, caudate and NAcc in striatum across hemispheres. These regions were chosen based on their relevance to our task: dlPFC has previously been demonstrated to be involved in executive processes and working memory (WM) and cognitive flexibility ( Barch et al, 2003 ; D'Esposito et al, 1995 ; Petrides, 2000 ; Plakke and Romanski, 2016 ), whereas vlPFC is thought to be important for goal-directed action and attention ( Levy and Wagner, 2011 ). vmPFC has been shown to be responsive to reward magnitude and reward probability in an overwhelming number of studies ( Rushworth et al, 2008 ).…”
Section: Materials and Methodsmentioning
confidence: 99%